Responsability of food industry, retailers and marketing in the prevention of obesity - Gomes, Ana (2011)
The incidence and prevalence of both pre‑obesity and obesity have been rising steadily throughout the world and, also, in Portugal. Estimates indicate that more than 50% of the world‑wide population will be obese in 2025 if specific measures are not taken, which justifies the fact that the World Health Organization has considered obesity as the global epidemic of the 21st century. Obesity emerges fundamentally as a consequence of successive positive energy balances, where the amount of energy ingested is superior to the amount of energy spent by the organism, although other factors must also be considered, namely, of genetic, cultural and behavioral origin The establishment of adequate prevention programs and their rigorous fulfillment can reduce the risk of pre‑obesity and obesity. Such programs are based on three basic pillars, namely, food, physical activity and change of behavior and need the involvement of all stakeholders, in particular of the family, the school, and the society where they are included. Equally determinative is the mobilizing role of food and drinks manufacturers, advertisers and traders who are called upon to revise their policies, both voluntarily and as a result of legislation. The global increase in highly processed food products high in calories compels the agro‑food industry and retailers, while responsible entities, to establish pledged and shared commitments aiming at the promotion of healthy eating habits.